Nuclear receptors: Lipid and hormone sensors with essential roles in the control of cancer development. (August 2021) - Font-Díaz, Joan; Jiménez-Panizo, Alba; Caelles, Carme; Vivanco, María dM; Pérez, Paloma; Aranda, Ana; Estébanez-Perpiñá, Eva; Castrillo, Antonio; Ricote, Mercedes; Valledor, Annabel F.
Abstract: Nuclear receptors (NRs) are a superfamily of ligand-activated transcription factors that act as biological sensors and use a combination of mechanisms to modulate positively and negatively gene expression in a spatial and temporal manner. The highly orchestrated biological actions of several NRs influence the proliferation, differentiation, and apoptosis of many different cell types. Synthetic ligands for several NRs have been the focus of extensive drug discovery efforts for cancer intervention. This review summarizes the roles in tumour growth and metastasis of several relevant NR family members, namely androgen receptor (AR), estrogen receptor (ER), glucocorticoid receptor (GR), thyroid hormone receptor (TR), retinoic acid receptors (RARs), retinoid X receptors (RXRs), peroxisome proliferator-activated receptors (PPARs), and liver X receptors (LXRs). These studies are key to develop improved therapeutic agents based on novel modes of action with reduced side effects and overcoming resistance.